A population-based comparison of BMI percentiles and waist-to-height ratio for identifying cardiovascular risk in youth - Kahn, Henry S.; Imperatore, Giuseppina; Cheng, Yiling J. (The Journal of pediatrics, 2005)
Determine whether waist-to-height ratio (WHtR) or sex- and age-specific percentiles of body mass index (BMI) better identifies cardiovascular risk. The third National Health and Nutrition Examination Survey (NHANES III) provided measurements on 7657 participants statistically weighted to represent 50.05 million youth 4 to 17 years of age. We estimated the subpopulations corresponding to BMI strata that were normal (<85th percentile), at risk for overweight (85th to <95th percentile), and overweight (≥95th percentile). We chose WHtR cutoff points (0.490 and 0.539) so that subpopulation sizes in the three WHtR strata would equal those in the three BMI strata. For 13 cardiovascular risk factors we compared mean levels among youth discordant for their BMI and WHtR strata. 726 participants (representing 3.69 million youth) were identified as having WHtR stratum >BMI stratum. Compared with the 603 participants (representing 3.70 million youth) who were discordant in the opposite direction, weighted analyses showed they had higher mean levels of heart rate, low-density lipoprotein (LDL) cholesterol, fasting triglycerides, and total cholesterol ( P <.015, adjusted for sex, age, and race-ethnicity). Their mean systolic blood pressure was lower, but this difference was eliminated after adjustment for their shorter stature. WHtR, a simpler anthropometric index than sex- and age-specific BMI percentiles, better identifies youth with adverse cardiovascular risk factors.